Competitive and seasonal oxidative stress in elite alpine ski racers - Schippinger, G.; Fankhauser, F.; Abuja, P. M.; Winklhofer-Roob, B. M.; Nadlinger, K.; Halwachs-Baumann, G.; Wonisch, W. (Scandinavian Journal of Medicine & Science in Sports, 2009)
We investigated competitive- and long-term oxidative stress during a competition season in eight top-ranked members of the Austrian Men's Alpine Ski Team. Serum total peroxides, antibody titers against oxidized LDL (oLAb) and lag time of the degradation of the fluorophore 1-palmitoyl-2-((2-(4-(6-phenyl-trans-1,3,5-hexatrienyl)phenyl)ethyl)-carbonyl)-sn-glycero-3-phosphocholine were measured, along with plasma concentrations of ascorbate, a- and ?-tocopherol, ß-carotene, uric acid and the lipid status. Competitive stress was indicated through an increased post-race uric acid level (286 ± 50 µM pre-race vs 456 ± 77 µM post-race, P<0.001) in December. Long-term effects were already apparent in November, with the highest concentrations of total peroxides (680 ± 458 µM H2O2 equivalents vs December 47 ± 58 µM H2O2 equivalents and January 15 ± 28 µM H2O2 equivalents, P<0.001) and a concomitant decrease in oLAb titers with an antibody trough in December (439 ± 150 mU/mL vs baseline 1036 ± 328 mU/mL; P=0.003). In January, after recovery, they attained nearly pre-season levels of oxidative stress biomarkers. This study indicates midseason oxidative stress in top-level skiers, which was associated with the performance in these athletes.